Lean Service management model to reduce canceled orders in a fast-food company - Avalos-Maldonado, Jazmin (2022)
The restaurant subsector is of great importance in the country's economy, generating a contribution of 2.8% of the national GDP. However, based on the research carried out, some problems that afflict the industry were identified, being the high rates of canceled orders the main problem that affects the study company. This problem results in customer dissatisfaction, so it is vitally important to reduce the causes that generate the cancellation of the client's orders. In relation to the above, the case study presents a high rate of returns surpassing the sector by 13.46% negatively impacting the profitability of the company. Therefore, a model based on the PDCA cycle was used, implementing Lean, BPM and FEFO Inventory Management tools with the aim of reducing canceled orders in the company. The implementation of these tools was carried out in different stages, taking as baseline the following indicators: percentage of overdue supplies, distance traveled, occupancy rate and level of satisfaction. At the end of the implementation, the % of cancelled orders was reduced by 9.7% and the percentage of overdue supplies decreased to 7.71%. In this way the distances traveled were reduced to 2255.6 meters improving the gross margin of the company. The result will be used as a reference and example for future implementations to the rest of the companies in the sector.